Are dairy cows with a more reactive temperament less efficient in energetic metabolism and do they produce more enteric methane? - Marçal-Pedroza, M. G.; Campos, M. M.; Sacramento, J. P.; Pereira, L. G.R.; Machado, F. S.; Tomich, T. R.; Paranhos da Costa, M. J.R. [UNESP]; Sant'Anna, A. C. (Elsevier, 2021)
It remains unknown whether dairy cows with more reactive temperament produce more enteric methane (CH4) and are less bioenergetically efficient than the calmer ones. The objectives of this study were (a) to evaluate the relationship between cattle temperament assessed by traditionally used tests with energetic metabolism and enteric CH4 emissions by crossbred dairy cows; (b) to assess how cows’ restlessness in respiration chambers affects energetic metabolism and enteric CH4 emissions. Temperament indicators were evaluated for 28 primiparous F1 Holstein-Gyr cows tested singly in the handling corral (entrance time, crush score, flight speed, and flight distance) and during milking (steps, kicks, defecation, rumination, and kick the milking cluster off). Cows’ behaviors within respiration chambers were also recorded for each individual kept singly. Digestibility and calorimetry trials were performed to obtain energy partitioning and CH4 measures. Cows with more reactive temperament in milking (the ones that kicked the milking cluster off more frequently) spent 25.24% less net energy on lactation (P = 0.04) and emitted 36.77% more enteric CH4/kg of milk (P = 0.03). Furthermore, cows that showed a higher frequency of rumination at milking parlor allocated 57.93% more net energy for milk production (P < 0.01), spent 50.00% more metabolizable energy for milk production (P < 0.01) and 37.10% less CH4/kg of milk (P = 0.04). Regarding the handling temperament, most reactive cows according to flight speed, lost 29.16% less energy as urine (P = 0.05) and tended to have 14.30% more enteric CH4 production (P = 0.08), as well as cows with a lower entrance time (most reactive) that also lost 13.29% more energy as enteric CH4 (P = 0.04). Temperament and restless behavior of Holstein-Gyr cows were related to metabolic efficiency and enteric CH4 emissions. Cows’ reactivity and rumination in the milking parlor, in addition to flight speed and entrance time in the squeeze chute during handling in the corral, could be useful measures to predict animals more prone to metabolic inefficiency, which could negatively affect the sustainability of dairy systems.
Keywords: Behavior; Holstein-Gyr; Personality; Restlessness; Sustainability